Concise account of recent S(N)2 ` grignard coupling reactions in organic synthesis - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
Over the past few decades studies oil controlling the chemo-, regio- and stereoselectivities of allylic Substitution reactions have been well documented in the literature and the S(N)2' Grignard coupling reaction has emerged as a very powerful tool ill selective carbon-carbon bond formation. This review focuses on all the recent synthetic developments in this special class of reactions. 1 Introduction 2 S(N)2' Grignard Coupling Reactions with Allylic Substrates 2.1 Allyl Halides 2.2 Allyl Acetates 2.3 Allyl Carbonates 2.4 Allyl Carbamates 2.5 Allyl Ethers 2.6 Allyl Silyl Ethers 2.7 Allyl Epoxides 2.8 Allyl Aziridines 2.9 Allyl Oxazolidinones 2.10 Allyl Thioethers 2.11 Allyl Benzotriazoles 2.12 Oxabicyclic Alkenes 2.13 Azabicyclic Alkenes 2.14 Oxa-azabicyclic Alkenes 3 S(N)2' Grignard Coupling Reactions with Propargyl Substrates 3.1 Propargyl Acetates 3.2 Propargyl Silyl Ethers 3.3 Propargyl Epoxides 3.4 Propargyl Aziridines 3.5 Propargyl Dithioacetals 3.6 Propargyl Thioethers 4 S(N)2' Grignard Coupling Reactions with Bromoallenes 5 S(N)2' Grignard Coupling Reactions in Natural/Unnatural Product Synthesis 6 Conclusions.
Keywords: allylic substrates; bromoallenes; chiral/achiral S(N)2 ` Grignard coupling reactions; Natural products; propargyl Substrates

Chemistry of recently isolated naturally occurring quinazolinone alkaloids - Mhaske, Santosh B.; N. P. Argade (Tetrahedron, 2006)
The present review portrays a concise account of the isolation, bioactivity, and synthesis of bioactive quinazolinone-based natural products for the period 1983-2005 and the recent developments in the area of complex quinazolinone natural products with a special emphasis on new synthetic routes and strategies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1983-2005; bioactivity; concise account; isolation; natural quinazolinones; synthesis

Chemoselective coupling reactions of 5,7-dimethoxyphthalide with the remotely functionalized alkyl iodides: facile racemic synthesis of helicobacter pylori antibiotics - Singh, Mandeep; N. P. Argade (Journal of Organic Chemistry, 2010)
Highly chemoselective coupling reactions of 5,7-dimethoxyphthalide carbanion with the remotely functionalized long chain alkyl iodides have been demonstrated to accomplish the concise and efficient synthesis of Helicobacter pylori antibiotics, the CJ-molecules, and sporotricale methyl ether.

Copper-catalyzed intramolecular N-arylation of quinazolinones: facile convergent approach to (-)-circumdatins H and J - Kshirsagar, Umesh A.; N. P. Argade (Organic Letters, 2010)
A copper-catalyzed intramolecular N-arylation of a quinazolinone nucleus that furnished the central benzodiazepine core unit has been demonstrated to accomplish an efficient convergent total synthesis of (-)-circumdatins H and J.

Chemoenzymatic total synthesis of potent HIV RNase H inhibitor (-)-1,3,4,5-tetragalloylapiitol - Batwal, Ramesh U.; Patel, Ramesh M.; N. P. Argade (Tetrahedron-Asymmetry, 2011)
Starting from racemic dimethyl 2-acetoxy-3-methylenesuccinate, the chemoenzymatic facile total synthesis of (-)-1,3,4,5-tetragalloylapiitol has been demonstrated via an efficient lipase catalyzed resolution followed by a DIBAL reduction-double gallyolation, osmium tetroxide dihydroxylation-double gallyolation, and reductive global O-benzyl deprotection pathway. (C) 2010 Elsevier Ltd. All rights reserved.

Concise account of the chemistry of valuable alkyl(methyl)maleic anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.
Keywords: alkyl(methyl)maleic anhydrides; bioactivity; dimethylmaleic anhydride; isolation; nucleophilic reactions; Total synthesis

Chemoenzymatic collective synthesis of optically active hydroxyl(methyl)tetrahydronaphthalene-based bioactive terpenoids - Batwal, Ramesh U.; N. P. Argade (Organic & Biomolecular Chemistry, 2015)
Starting from succinic anhydride and 2-methylanisole, a chemoenzymatic collective formal/total synthesis of several optically active tetrahydronaphthalene based bioactive natural products has been presented via advanced level common precursors; the natural product and antipode (-)/(+)-aristelegone B. Regioselective benzylic oxidations, stereoselective introduction of hydroxyl groups at the alpha-position of ketone moiety in syn-orientation, efficient enzymatic resolutions with high enantiomeric purity, stereoselective reductions, samarium iodide induced deoxygenations and tandem acylation-Wittig reactions without racemization and/or eliminative aromatization were the key features. An attempted diastereo-selective synthesis of (+/-)-vallapin has also been described.

Chemoenzymatic access to (+)-artabotriol and its application in collective synthesis of (+)-grandiamide D, (-)-tulipalin B, (+)-spirathundiol, and (+)-artabotriolcaffeate - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2016)
Starting from dimethyl (+/-)-2-hydroxy-3-methylenesuccinnate chemoenzymatic collective formal/total synthesis of enantiomerically pure bioactive natural products has been described via the advanced level common precursor (+)-artabotriol. An efficient enzymatic resolution with high enantiomeric purity, selective diester to diol reduction, and requisite dehydrative coupling reactions without any racemization are the significant topographies.
Keywords: (+)-artabotriol; collective synthesis; coupling reactions; dimethyl (+/-)-2-hydroxy-3-methylenesuccinate; Enzymatic resolution; Natural products; reduction